The Artistry of Afro-Cuban Batá Drumming : Aesthetics, Transmission, Bonding, and Creativity - Schweitzer, Kenneth George (Book collections on Project MUSE., 2013)
An iconic symbol and sound of the Lucumi/Santeria religion, Afro-Cuban bata are talking drums that express the epic mythological narratives of the West African Yoruba deities known as orisha. By imitating aspects of speech and song and by metaphorically referencing salient attributes of the deities, bata drummers facilitate the communal praising of orisha in a music ritual known as a toque de santo. In The Artistry of Afro-Cuban Bata Drumming, Kenneth Schweitzer blends musical transcription, musical analysis, interviews, ethnographic descriptions, and observations from his own experience as a ritual drummer to highlight the complex variables at work during a live Lucumi performance. Integral in enabling trance possessions by the orisha, by far the most dramatic expressions of Lucumi faith, bata drummers are also entrusted with controlling the overall ebb and flow of the four- to six-hour toque de santo. During these events, bata drummers combine their knowledge of ritual with an extensive repertoire of rhythms and songs. Musicians focus on the many thematic acts that unfold both concurrently and in quick succession. In addition to creating an emotionally charged environment, playing salute rhythms for the orisha, and supporting the playful song competitions that erupt between singers, bata drummers are equally dedicated to nurturing their own drumming community by creating a variety of opportunities for the musicians to grow artistically and creatively.